Answer:
The answer to your question is a) 10 u b) [tex]\sqrt{5}[/tex] u
Step-by-step explanation:
Data
a) ( -6, 0)
(0, 8)
b) (1, 6)
( 0, 4)
Formula
d = [tex]\sqrt{(x2- x1)^{2} + (y2 - y1)^{2}}[/tex]
Substitution, simplification and result
a) d = [tex]\sqrt{(0 +6)^{2}+ (8 - 0)^{2}}[/tex]
d = [tex]\sqrt{6^{2}+ 8^{2}}[/tex]
d = [tex]\sqrt{100}[/tex]
d = 10 u
b) d = [tex]\sqrt{(4 - 6)^{2}+ (0 - 1)^{2}}[/tex]
d = [tex]\sqrt{(-2)^{2} + (-1)^{2}}[/tex]
d = [tex]\sqrt{4 + 1}[/tex]
d = [tex]\sqrt{5}[/tex]